2016
DOI: 10.1159/000448080
|View full text |Cite
|
Sign up to set email alerts
|

The Pioneering and Unknown Stereotactic Approach of Roeder and Orthner from Göttingen. Part I. Surgical Technique for Tailoring Individualized Stereotactic Lesions

Abstract: During the 1950s through the 1970s, Hans Orthner and Fritz Roeder, two German neurologists from Göttingen, developed a sophisticated technique to perform functional stereotactic surgery with outstanding accuracy. They introduced direct air ventriculography performed in the same surgical session as the ablative stereotactic procedure. For individualized surgical targeting, Orthner prepared a stereotactic atlas (>60 brains) with an ingenious brain-slicing device, the Göttinger macrotome. Brains were grouped base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…while in our study patients were usually aged and no cause of exposure was found, mostly it was idiopathic while in other Almost all patients had improvement intheir symptoms and a decrease in medication dose, some with minimal to moderate complication. The pallidotomy significantly improves the symptoms and improved the daily life activities of the patient as it is seen in many studies that pallidotomy has markedly modified symptoms of Parkinson's disease like dyskinesia, rigidity and tremor [12,13,14] .From the experience through multiple studies, it is gained that bilateral pallidotomy can have negative impact like swallowing, speech and cognition defect which can lead to depression [15] .Therefore, we performed all our cases unilaterally, to get over such complications. Keep close observation, studies have shown that overall, 25 % to 35% percent reduction is seen in UPDRS III motor score in the duration of 6 months clinical follow-up [13] .…”
Section: Discussionmentioning
confidence: 96%
“…while in our study patients were usually aged and no cause of exposure was found, mostly it was idiopathic while in other Almost all patients had improvement intheir symptoms and a decrease in medication dose, some with minimal to moderate complication. The pallidotomy significantly improves the symptoms and improved the daily life activities of the patient as it is seen in many studies that pallidotomy has markedly modified symptoms of Parkinson's disease like dyskinesia, rigidity and tremor [12,13,14] .From the experience through multiple studies, it is gained that bilateral pallidotomy can have negative impact like swallowing, speech and cognition defect which can lead to depression [15] .Therefore, we performed all our cases unilaterally, to get over such complications. Keep close observation, studies have shown that overall, 25 % to 35% percent reduction is seen in UPDRS III motor score in the duration of 6 months clinical follow-up [13] .…”
Section: Discussionmentioning
confidence: 96%
“…The unique stereotactic approach of the Göttingen group based on head and brain (ventriculographic) measurements and Orthner’s stereotactic atlas has been reviewed in detail [23]. After lessons had been learned from, for example, staged pallidal lesioning for hemiballism [24] (Fig.…”
Section: Target Definition In the Pallidummentioning
confidence: 99%
“…They regarded the pallidum as “structurally intact and healthy,” but “hyperactive” and “disinhibited” (authors’ translation), and, by reasoning in terms of pathological projection systems, they attempted to interrupt its outflow [15]. Stimulation and lesioning were made exclusively with string electrodes, although rod (straight needle) electrodes had already become more popular at that time [23] (online suppl. material String Electrodes).…”
Section: Target Definition In the Pallidummentioning
confidence: 99%